The Effect of Fear Of Missing Out and Financial Literacy on Student Financial Behavior - John Wijayanto; Manuel A. Todingbua; Amir Jaya (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Students today face a number of difficulties when it comes to handling their finances in the digital age. Anxiety or worry about missing out on exciting opportunities or social interactions is known as FOMO, and it is one of the newer phenomena. FOMO is frequently brought on by social media, where people can be influenced to engage in consumerist behavior by seeing their friends buying new things or taking part in different activities. The mental health of Generation Z is significantly impacted by FOMO as well. High levels of stress, anxiety, and feelings of inadequacy can result from the pressure to constantly be online and actively participate in social media. They constantly compare themselves to others they observe in their daring lives, which frequently leads them to conclude that many aspects of their lives that are shared on social media are representations that are dissimilar from reality. Fear of Missing Out (FOMO) has a positive and significant impact on financial behavior. Financial literacy has a positive and significant impact on financial transactions. The research methodology used is quantitative research employing validity tests, reliability tests, linear regression, t-tests, correlation, and determination of significant and positive influence in the financial management study of the Management Study Program at the Faculty of Economics and Business at Universitas Kristen Indonesia Paulus. The variable X1, or fear of missing out, has a significant impact on the financial performance of the students in the Program of Study Management at the Faculty of Economics and Business at Universitas Kristen Indonesia Paulus. The financial literacy variable, also known as X2, has a significant and positive impact on the financial literacy of the Program Study Management Faculty of Economics and Business at Universitas Kristen Indonesia Paulus.